Satisfaction with life among public and private university students in Sabah, Malaysia: A modification scale using factor analysis - Mohd. Dahlan A. Maleka; Adeymend Reny Japil; Mahirah Masdina; Muhammad Idris Bullare @ Bahari; Adi Fahrudin; Alfred Chan Huan Zhi; Lailawati Madlan Endalan; Nur Farhana Ardillah Aftar; Ida Shafinaz Mohamed Kamila; Husmiati Yusuf (Malque Publishing, 2023)
This research intended to develop a valid and reliable instrument of the Satisfaction with Life Scale (SWLS) to measure satisfaction with life (SWL) constructs among public and private university students in Sabah, Malaysia, through the exploratory factor analysis (EFA) procedure. The pilot study obtained a sample of 108 students from public and private education institutions in Sabah, Malaysia, through an online survey using a self-administered questionnaire. The researchers performed the EFA procedure on SWL construct using IBM SPSS 25. The Bartletts' Test of Sphericity is highly significant (Sig. = .000). Furthermore, the sampling adequacy by Kaiser‒Meyer‒Olkin (KMO = 0.839) is excellent. Using the extraction method of Principal Component Analysis (PCA) with Varimax Rotation, a component of the SWL construct is extracted with an eigenvalue of 3.101. The variance explained for this component is 62.030%. The construct of SWL has Cronbach's alpha value of .817. The development scale and validation confirmed that the instrument is consistent and stable with both private and public college and university student samples. It adds a remarkable contribution to the measurement of SWLS, mainly in the context of higher education institution students. The EFA outcomes formed a configuration that extracts a component of SWL, which can be measured by the original five items established in this research. This research reveals that the SWL construct is applicable in this study.